Nitrogen dynamics in soil Treated with plant-growth promoting bacteria and urea fertilizer - Akter, Amaily; Ali Tan, Kee Zuan; Kasim, Susilawati; Mohd Amin, Adibah; Ab Aziz, Zakry Fitri; Md Rahmatullah, Noor; Sadeq, Buraq Musa; Chompa, Sayma Serine; Rahman, Md Ekhlasur (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2023)
The mineralization of urea fertilizer significantly impacts nitrogen movement in the soil. An incubation study was done on a lab scale basis to examine nitrogen dynamics in soil inoculated with plant growth-promoting bacteria (PGPB) supplemented with varying levels of N-fertilizer in the form of urea (0 N, 25N, 50N, 75N and 100 N). In the present experiment, sandy clay loam soil was used and incubated for four weeks, and the concentrations of NH4+-N and NO3--N were monitored using the destructive method (Kjeldahl) to determine the mineralization rate of urea. Results showed higher NH4+-N (11.880 mg/kg mineralized with UPMRB9N50 treatment) and NO3--N (20.060 mg/kg mineralized with UPMRB9N50 treatment) concentrations in the bacteria-treated soil compared to the uninoculated control. Urea-N remains higher (0.0353 and 0.0253 from UPMRB9N50 treatment in the first and second weeks, respectively) in bacteria-treated soil during the first two weeks, then gradually became zero towards the end of the observing period. Nitrogen leaching loss was lower in bacterial inoculated soil compared to the control, and leaching loss of N was greater with the increased N fertilizer rates. Cumulative N leaching loss is higher (29.797 mg/kg) in 100N treated soil than in other treatments. The findings observed that the beneficial bacteria could enhance the N mineralization to make the nutrient available for the crop, while at the same time, reducing leaching losses of fertilizer, when supplied with a minimum amount of the chemical fertilizer, thereby saving the input cost and protecting the environment.